The effect of depth on drag during the gliding phase in swimming - Marinho, D.A. (2011)
The gliding phase following a swimming start or turn is an important component of the overall swimming performance. PURPOSE: To analyse the effect of depth on hydrodynamic drag force during the underwater gliding, using computational fluid dynamics. METHODS: A three-dimensional domain was created to simulate the fluid flow around a swimmer model, representing the geometry of part of a lane in a swimming pool. The water depth of this domain was 1.50 m with a 3.0 m width and 11.0 m length. Computational fluid dynamics methodology was used to perform numerical simulations in the created domain which was divided into a number of mesh cells. The k-epsilon turbulent model was applied to the flow around a three-dimensional model of a male adult swimmer in a prone gliding position with the arms extended at the front. General moving object model was used to simulating the body as the displacing object. During the gliding, the swimmer model’s middle line was placed at three different water depths: at 0.20 m (just under the surface), at 0.75 m (middle of the pool), and at 1.30 m (bottom of the pool). The drag coefficient and the hydrodynamic drag force were computed using a steady velocity of 2.50 m/s for the different depths run for 3 s in each case. RESULTS: The drag coefficient was 0.37, 0.34 and 0.30 and the drag force was 141.40 N, 128.10 N and 115.30 N when gliding at a water depth of 0.20 m, 0.75 m and 1.30 m, respectively, at the time of 2 s when the swimmer was approximately at the middle of the computational pool. CONCLUSIONS: The hydrodynamic drag values for the gliding decreased with the increase in depth. This decrease of drag values with depth can be due to the reduction of the wave drag effect, which has an important contribution to total drag near the water surface. Reducing the drag experienced by swimmers during the glide off the wall can decrease start and turn times and unnecessary energy loss. Hence, these results suggested that gliding at 0.75 m under the water surface or deeper seemed to be an optimal gliding depth for minimizing drag and improve swimming performance